Betahistine plus piracetam dual therapy versus betahistine monotherapy for peripheral vestibular vertigo: a confounder-corrected subanalysis of the OSVaLD study. (2nd November 2015) - Melnikov, Oleg A.; Lilenko, Sergey V.; Nauta, Jos; Ouwens, Mario J.N.M.
Abstract: Introduction: This subanalysis compared the efficacy of betahistine plus piracetam dual therapy versus betahistine monotherapy using data from OSVaLD, a 3 month, open-label, observational study conducted in 2272 patients with peripheral vestibular vertigo. Of the 1898 patients included in the original efficacy population, 1076 were from countries where betahistine plus piracetam dual therapy was prescribed to >1 patient; 114 of these 1076 patients (11%) received the dual therapy and 567 (53%) were treated with betahistine monotherapy; these patients were selected for analysis. Methods: Efficacy was assessed using the Dizziness Handicap Inventory (DHI) total and subscale scores. Propensity-score matching was used to correct potential differences in patient baseline characteristics between treatment groups. In addition, a subgroup analysis evaluated 103 patients treated with betahistine because of insufficient efficacy with their existing treatment. Results: In the propensity-score matched, total-population evaluation, improvements in the DHI total and subscale scores were numerically greater in the betahistine plus piracetam group ( n  = 88) versus the betahistine group ( n  = 89) (DHI total, −42.9 vs. −37.6, respectively; DHI physical, −12.1 vs. −10.4; DHI emotional, −13.5 vs. −13.2) and statistically significant for the DHI functional score (−17.3 vs. −14.0, respectively, p  = 0.01). The percentage of patients with no impairment at final visit was 27% with betahistine and 47% with betahistine plus piracetam; odds ratio: 2.3, 95% confidence interval: 1.3–2.4 ( p  = 0.007). Similar results were obtained in the subgroup analyses for patients whose current vertigo treatment was insufficient. The overall incidence of adverse events was low and similar in both groups, and there were no discontinuations due to drug-related adverse events. Conclusions: By using propensity-score matching, which controls for potential heterogeneity in patient baseline characteristics and small patient numbers, the results of this analysis suggest that combined betahistine and piracetam may be more effective than betahistine alone in patients with peripheral vestibular vertigo.